The Attitudes of University Students of Batubara in Medan Towards Batubara Malay Language - Julisah Izar; Siti Aisah Ginting (LINGUISTIK TERAPAN, 2016)
This study dealt with the attitudes of university students of Batubara towards Batubara Malay language. The data were collected from 20 university students of Batubara in Medan. The instruments used for collecting the data were observation sheet, questionnaire sheet and depth interview. The data were analyzed by Moleong’s theory. The findings showed that the respondents’ attitudes were: 12 (60%) negative and 8 (40%) positive. The attitudes levels of university students included in negative and positive attitudes namely in: receiving 11 (55%) negative and 9 (45%) positive, responding 12 (60%) negative and 8 positive, valuing 10 (50%) negative and 10 (50%)  positive,  organizing 12 (60%) positive and 8 (40%) negative, and internalizing values 12 (60%) negative and 8 (40%) positive. The factors influenced the university students’ attitudes were language disloyalty 12 (60%) negative and 8 (40%) positive, language pride lack 14 (70%) negative and 7 (30%) positive, in the unawareness of the norms 11 (55%) negative and 9 (45%) positive. Bahasa Indonesia is dominantly spoken by the university students of Batubara in Medan which caused they have less frequency in using their Batubara Malay language with their friends who are from same region in Medan. Key words: Attitudes, University Students of Batubara, Batubara Malay Language